PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE THINK-PAIR-SHARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA 1 SMA NEGERI 1 PARIGI UTARA PADA MATERI OPERASI HITUNG MATRIKS: Aplication Of The Think-Pair-Share Type Cooperative Learning Model To Improve The Learning Outcomes Of Class XI IPA 1 Students at SMA Negeri 1 North Parigi On Matrix Arithmetic Operations Material - Azmi, Nurul; Rizal, Muh.; Nurhayadi (Universitas Tadulako, 2024)
The purpose of this study was to obtain a description of the application of the Think-Pair-Share (TPS) cooperative learning model which can improve learning outcomes on matrix count operations in class XI IPA 1 SMA Negeri 1 Parigi Utara. This research is a collaborative classroom action research which refers to the research design of Kemmis and MC. Taggart, namely (1) planning, (2) implementation of action, (3) observation and (4) reflection. The subjects of this study were students of class XI IPA 1 SMA Negeri 1 Parigi Utara. This research was conducted by following the steps of the think pair share (TPS) cooperative learning model, namely 1) giving students' perceptions and motivation, 2) dividing students into small groups of students consisting of 2 people per group, 3) presenting information and ask questions, (4) think individually (think), (5) discuss with group friends (pairs), (6) share the results of discussions with group friends (share), (7) draw conclusions, (8) evaluate. The results showed that learning by applying the think-pair-share type of cooperative learning model could improve students 'mathematical understanding skills as indicated by the change in students' knowledge in cycle I for the better in cycle II. Changes in student knowledge can be seen from the results of the final test analysis of students' actions in the first cycle of 43.75% and an increase in the second cycle of 90.91%.